Exercising Interest in the Middle Age Group - Jeki Haryanto; Wilda Welis (Universitas Negeri Padang, 2019)
This research begins with a phenomenon that occurs in Air Hangat Subdistrict, Kerinci Regency, which shows that a lack of interest to do sport in the middle age group (45-59 years old). This study aims to find out how interested this age group is in exercising. This type of research is a cross-sectional survey research that is describes a particular situation or situation as it is with the process of taking data only takes place at one time. The subjects in this study are the elderly who are in the middle age category, namely the elderly who are in the age range of 45 - 59 years who do sports in the Air Hangat subdistrict of Kerinci Regency (N=33). The sampling technique used in this research is sensus sampling which mean making the entire population as a sample. The data in this study was collocted using a Guttman scale questionnaire. The data is analysed using descriptive statistics. Based on the results of data analysis, it shows that the interest of the elderly in the middle age group to exercise is in the sufficient category. This is due to the lack of knowledge and role of the family, so their interest needs to be increased again with the hope that in the future this age group will be healthier.